Cataloguing information agenda for the millennium in Nigerian libraries (2002)
This paper conceptualised the creation of an online national bibliographic network in Nigeria as the cataloguing and classification information agenda for the new millennium. To this end, a virile and efficient communication network system that will enhance the linkage of databases from the local, through zonal offices, to the national level is proposed as a preparatory step to ultimately connecting the international grid of databases. The continued relevance of cataloguers in professional practices is established. The attendant problems of "biblio-technovolution" are examined, while the roles of the federal government of Nigeria, the Nigeria library association, the national library of Nigeria, other library institutions, commercial agencies and individual librarians in meeting the challenges occurring in the business of creating access to the world of information is discussed.